The influence of some interfacial properties of PEO-b-PPO copolymers on dewatering of water-in-oil asphaltene model emulsions - Ramalho, Joao Batista; Ramos, Natalie; Lucas, Elizabete (Publishing House of Lviv Polytechnic National University, 2009)
Three different macromolecular structures of poly(ethylene oxide-b-propylene oxide) copolymers, used in formulations of commercial demulsifiers for breaking water-in-crude oil emulsions, were investigated. The interfacial activity (a), the lower interfacial tension (gm), the critical micelle concentration (CMC), the interfacial concentration (Ґ) and the molecular area (A) adsorbed at the interface of the surfactant solutions were evaluated. These results were correlated to surfactant performance in coalescing three different asphaltene model emulsions. The PEO-b-PPO commercial demulsifiers, that were capable to dewater asphaltene model emulsions, exhibited interfacial activity to the oil-water interface, reduced the interfacial tension to low values, reached the CMC at low concentration and presented low molecular area adsorbed at the interface. Досліджено три різних макромолекулярних структури полі(оксид етилену-b-оксид пропілену) кополімерів, які входять до складу промислових деемульгаторів для руйнування емульсій вода-сира нафта. Визначені такі величини, як активність на поверхні розділу, нижній міжфазний натяг, критичну концентрацію міцели (СМС), міжфазну концентрацію і площі, які займають адсорбовані молекули на розділі фаз. Отримані результати встановлюють співвідношення між поверхнево-активними властивостями трьох різних асфальтенових модельних емульсій. Показано, що промислові деемульгатори РЕО-b-PPO, здатні зневоднювати такі емульсії, виявляють активність на поверхні розділу вода-нафта, знижують міжповерхневий натяг, досягають СМС при малих концентраціях і малій площі, яку займають молекули на поверхні розділу фаз.
Вплив міжфазних властивостей РЕО-b-PPO кополімерів на зневоднення асфальтенових модельних емульсій вода-нафта
Keywords: crude oil; dewatering; demulsifier; polyoxides; asphaltenes; interfacial tension; сира нафта; зневоднення; деемульгатор; поліоксиди; асфальтени; міжфазний натяг